Perlindungan Hukum Bagi Anggota Dan Nasabah Koperasi Simpan Pinjam - Tuhumury*, Harry A; Tuharea, Farida; M Roem, Anwar; Irsan, Irsan; Latuheru, Anita (Universitas Syiah Kuala, 2023)
The purpose of this paper is to determine the legal protection for members and customers of savings and loan cooperatives. The methodology used in this paper is normative research, which examines legal provisions, legal principles, and legal doctrines in order to address legal issues with a statute approach and a conceptual approach. Legal protection for cooperative members is very important, because legal protection is a guarantee against actions taken by cooperative management outside their authority. Legal protection can also be given to savings and loan cooperative customers if they are appointed as members of the cooperative, because cooperative customers are prospective members of savings and loan cooperatives.